Oxygen-Generating Photo-Cross-Linkable Hydrogels Support Cardiac Progenitor Cell Survival by Reducing Hypoxia-Induced Necrosis - ALEMDAR YAYLA, NESLİHAN (AMER CHEMICAL SOC, 2017)
Oxygen is essential to cell survival and tissue function. Not surprisingly, ischemia resulting from myocardial infarction induces cell death and tissue necrosis. Attempts to regenerate myocardial tissue with cell based therapies exacerbate the hypoxic stress by further increasing the metabolic burden. In consequence, implanted tissue engineered cardiac tissues suffer from hypoxia-induced cell death. Here, we report on the generation of oxygen-generating hydrogels composed of calcium peroxide (CPO) laden gelatin methacryloyl (GelMA). CPO-GeIMA hydrogels released significant amounts of oxygen for over a period of 5 days under hypoxic conditions (1% O-2). The released oxygen proved sufficient to relieve the metabolic stress of cardiac side population cells that were encapsulated within CPO-GelMA hydrogels. In particular, incorporation of CPO in GelMA hydrogels strongly enhanced cell viability as compared to GelMA-only hydrogels. Importantly, CPO-based oxygen generation reduced cell death by limiting hypoxia-induced necrosis. The current study demonstrates that CPO based oxygen-generating hydrogels could be used to transiently provide oxygen to cardiac cells under ischemic conditions. Therefore, oxygen generating materials such as CPO-GelMA can improve cell-based therapies aimed at treatment or regeneration of infarcted myocardial tissue.
Keywords: cell survival; implantation; avascular; tissue engineering; stem cells; controlled release; oxygen evolution; biomaterials; STEM-CELLS; MYOCARDIAL-INFARCTION; IN-VITRO; TISSUE; HEART; TRANSPLANTATION; GELATIN; REPAIR; BIOMATERIALS; REGENERATION